2010
DOI: 10.1080/01446191003725154
|View full text |Cite
|
Sign up to set email alerts
|

Who reads the project file? Exploring the power effects of knowledge tools in construction project management

Abstract: Various critical authors have questioned the salience, efficacy and power effects of formal project management bodies of knowledge (PMBoKs). As a result project management knowledge tools are increasingly being conceptualized along more flexible, adaptable, reflexive, democratic and informal terms. A central driver for this shift is that PM knowledge will be more relevant and useful for practitioners if it can be reflexively tailored to fit local project scenarios, emergent problems and different communities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…One possible method could be to compare project performance where there is a high degree of cohesion with corporate strategic intent and those with increased diffusion. It might be assumed that those projects with a high degree of strategic alignment are most successful in performative terms; however as many other practice-studies of construction have shown local adaptation to top-down initiatives can equally prove advantageous, or necessary, in certain settings (Bresnen, 2009;Harty, 2008;Sage et al 2010). By addressing such questions, SaP studies of construction strategizing can help equip reflective practitioners with an awareness of the plethora of strategic trajectories, (along with a keen awareness of the role that all practitioners play in strategic praxis) which would provide individuals at the start of a strategic implementation within an organization with valuable insights to insure that the final articulations of strategy, and their performance outcomes, more closely resembled the beneficial states they wishes to obtain.…”
Section: Discussion and Concluding Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible method could be to compare project performance where there is a high degree of cohesion with corporate strategic intent and those with increased diffusion. It might be assumed that those projects with a high degree of strategic alignment are most successful in performative terms; however as many other practice-studies of construction have shown local adaptation to top-down initiatives can equally prove advantageous, or necessary, in certain settings (Bresnen, 2009;Harty, 2008;Sage et al 2010). By addressing such questions, SaP studies of construction strategizing can help equip reflective practitioners with an awareness of the plethora of strategic trajectories, (along with a keen awareness of the role that all practitioners play in strategic praxis) which would provide individuals at the start of a strategic implementation within an organization with valuable insights to insure that the final articulations of strategy, and their performance outcomes, more closely resembled the beneficial states they wishes to obtain.…”
Section: Discussion and Concluding Commentsmentioning
confidence: 99%
“…However, it also indicates vindicates Latour's (2005) proposal that material objects can no more bring about social change by themselves than people can. Indeed various studies of construction have demonstrated that objects do not upon people or vice versa but rather agency is located between them, this is no less true of lean construction than 3D-CAD (Harty, 2008) or construction project management (Sage et al 2010). …”
Section: Lean Strategizing On Sitementioning
confidence: 99%
“…ANT studies have illustrated the transformative role of nonhumans to the co-ordination of projects, and managerial power (Blackburn, 2002;Linde and Linderoth, 2006;Pollack et al, 2013), not least in the context of construction (Harty, 2005;Sage et al, 2010b;Tryggestad et al, 2010). Bruno Latour (2005: 88), one of the originators of ANT (along with John Law and Michel Callon), even heralds building sites as exemplars of ANT: the transformative symbiosis of humans and nonhumans (see Latour and Yaneva, 2008).…”
Section: Materials (Re)distributions Of Project Failurementioning
confidence: 99%
“…Chan illustrated that there are also not only human but non-human influencing factors in the success of the construction project [15]. Study of the actor-network suggests that engineering activities, with both technical and non-technical content [17], are the situational practices that combine together to form a conceptual and political power network [16,18]. Engineering activity is an integrated process of heterogeneous elements which are not given and freely available for innovators.…”
Section: Introductionmentioning
confidence: 99%